Kajian Kerentanan Wilayah Pesisir Ditinjau dari Geomorfologi dan Elevasi Pesisir Kota dan Kabupaten Jayapura, Provinsi Papua - Baigo Hamuna; Annisa Novita Sari; Alianto Alianto (Jurnal Wilayah dan Lingkungan, 2018)
The coastal areas of both Jayapura Municipality and Regency which is directly opposite to the Pacific Ocean with the multifunctional use is a vulnerable area to disasters. The coastal vulnerability is determined by considering some influential factors, that is geomorphology and elevation to minimize the coastal damage impacts. The purpose of this study is to determine the coastal vulnerability index of Jayapura City and Regency focusing on the coastal geomorphology and elevation. The study area covers a coastal area of 241.86 km along the coastlines of Jayapura Municipality and Regency. The study method includes data collection on the coastal geomorphology and elevation characteristics. The value of coastal vulnerability index of each parameter is determined by dividing into five categories of coastal vulnerability. The result shows territorial division as follows: 145.88 km (61.18%) was not vulnerable, 33.14 km (13.90%) was less vulnerable, 29.03 km (12.17%) was a moderate vulnerability, 12.12 km (5.08%) was vulnerable, and the remaining 18.29 km (7.67%) was very vulnerable. The coastal vulnerability of Jayapura City coastal areas categorized into three classes, i.e. not vulnerable, moderate vulnerable and vulnerable, while the Jayapura Regency coastal areas felt into the following classes: not vulnerable and moderate vulnerable. The most vulnerable areas were of Abepura District, South Jayapura District and Muaratami District, all in the Jayapura Municipality administration. Those areas with high elevation level were not vulnerable at all.